2013
DOI: 10.1590/s0004-27492013000600003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotorsion measurement in laser refractive surgery

Abstract: Artigo Original | Original article INTRODUCTIONAstigmatism is a common refractive error that generates multiple focal points over the retina. It's frequently caused by an asymmetry in the corneal curvature. When the two corneal meridians are at right angle, the ametropia can be corrected with spectacles (regular astigmatism). When there are irregularities in the meridians or they are not at right angle, it's called irregular astigmatism, and does not allow correction with spectacles (1) .Mild torsional alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, the findings had important clinical relevance, since 3 degrees of IOL deviation cause an approximate loss of 10% of astigmatism correction [3]. Moreover, with an increase in astigmatism, the impact of a change in the position of the eye due to cyclotorsion on the correction is greater [12].…”
Section: Discussionmentioning
confidence: 93%
“…However, the findings had important clinical relevance, since 3 degrees of IOL deviation cause an approximate loss of 10% of astigmatism correction [3]. Moreover, with an increase in astigmatism, the impact of a change in the position of the eye due to cyclotorsion on the correction is greater [12].…”
Section: Discussionmentioning
confidence: 93%
“…35 Studies have shown that when eye cyclotorsion is greater than 2 degrees and not compensated, cylinder correction might be adversely influenced and significant aberrations can be induced during laser treatment, especially in patients with high astigmatism. 68 Currently, with the rapid development of refractive surgical technology, personally designed laser platform surgery equipped with pupil-tracking or iris-registration software allows for more precise, safe, and predictable corneal ablation in refractive correction than ever before. However, no acknowledged method of cyclotorsion compensation exists for the VisuMax femtosecond laser system (Carl Zeiss Meditec, Jena, Germany).…”
mentioning
confidence: 99%